CURRENT TENDENCIES REGARDING THE TOURISTIC INFRASTRUCTURE OF DRĂGOIASA-TULGHEŞ DEPRESSION ALIGNMENT - George-Bogdan TOFAN (Analele Universităţii din Oradea: Seria Geografie, 2013)
The study at hand deals with a relatively small region (790 km2 ), that, from an administrative point of view, encapsulates the territory of Drăgoiasa, Păltiniş, Glodu and Catrinari villages, belonging to Panaci Commune, Suceava County, and Bilbor commune, Secu, a locality of the City of TopliŃa, the City of Borsec, and Corbu and Tulgheş communes, all situated in the northern part of Harghita County. The touristic infrastructure contains the ensemble of therapeutic, recreational, food and transport elements, whose purpose is to satisfy touristic demand. The aim of this study is to present aspects regarding the main touristic infrastructures, mainly concentrated in Borsec, the oldest of the Eastern Carpathians, which has seen a dramatic decrease in touristic activity, in the last two decades. The accommodation infrastructure mostly remained at the same level as during the interwar years by exclusively maintaining the villa system (until 2001), which only recently went through a restoration process. This led to fewer and fewer demands. This status quo was further exacerbated by precarious connections, which involve transbordations.